Early outcomes and risk factors in orthognathic surgery for mandibular and maxillary hypo- and hyperplasia: a 13-year analysis of a multi-institutional database - Knoedler, Samuel; Baecher, Helena; Hoch, Cosima C.; Obed, Doha; Matar, Dany Y.; Rendenbach, Carsten; Kim, Bong-Sung; Harhaus-Wähner, Leila; Kauke-Navarro, Martin; Hundeshagen, Gabriel; Knoedler, Leonard; Orgill, Dennis P.; et al. (Journal of Clinical Medicine, 2023)
Background: Orthognathic surgery (OS) is a frequently performed procedure for the correction of dentofacial deformities and malocclusion. Research on OS is mostly limited to single-surgeon experience or single-institutional reports. We, therefore, retrospectively analyzed a multi-institutional database to investigate outcomes of OS and identify risk factors for peri- and postoperative complications. Methods: We reviewed the American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) database (2008-2020) to identify patients who underwent OS for mandibular and maxillary hypo- and hyperplasia. The postoperative outcomes of interest included 30-day surgical and medical complications, reoperation, readmission, and mortality. We also evaluated risk factors for complications. Results: The study population included 674 patients, 48% of whom underwent single jaw surgery, 40% double jaw surgery, and 5.5% triple jaw surgery. The average age was 29 ± 11 years, with an equal gender distribution (females: n = 336; 50%, males: n = 338; 50%). Adverse events were relatively rare, with a total of 29 (4.3%) complications reported. The most common surgical complication was superficial incisional infection (n = 14; 2.1%). While the multivariable analysis revealed isolated single lower jaw surgery (p = 0.03) to be independently associated with surgical complication occurrence, it also identified an association between the outpatient setting and the frequency of surgical complications (p = 0.03) and readmissions (p = 0.02). In addition, Asian ethnicity was identified as a risk factor for bleeding (p = 0.003) and readmission (p = 0.0009). Conclusion: Based on the information recorded by the ACS-NSQIP database, our analysis underscored the positive (short-term) safety profile of OS. We found OS of the mandible to be associated with higher complication rates. The calculated risk role of OS in the outpatient setting warrants further investigation. A significant correlation between Asian OS patients and postoperative adverse events was found. Implementation of these novel risk factors into the surgical workflow may help facial surgeons refine their patient selection and improve patient outcomes. Future studies are needed to investigate the causal relationships of the observed statistical correlations.